Use of Radiobiological Modeling in Treatment Plan Evaluation and Optimization of Prostate Cancer Radiotherapy - Mavroidis, Panayiotis; Baltas, Dimos; Lind, Bengt K.; Papanikolaou, Nikos (IntechOpen, 2011)
None